2021
DOI: 10.6004/jnccn.2020.7797
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Care Associated With Non–English-Speaking Patients With Breast Cancer

Abstract: Background: Breast cancer care requires coordination between multiple diagnostic and treatment modalities. Disparities such as age, race/ethnicity, and socioeconomic status are associated with delays in care. This study investigates whether primary language is associated with delays in breast cancer diagnosis and treatment before and through radiotherapy (RT). Patients and Methods: This study was an institutional retrospective matched-cohort analysis of women treated with breast RT over 2 years. A total of 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This study identified that non‐English speakers had a lower rate of DLI closure at the 6‐month mark compared to English speaking patients (7.7% vs. 36.8%, P = 0.028). A non‐English primary language has been found to be risk factor with regard to access to elective surgery in diverticular disease 34 as well as a risk factor for delayed treatment in breast cancer care 35 . Qualitative data from colorectal cancer survivors demonstrates that non‐English speaking patients experience a perception of discrimination in accessing healthcare 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified that non‐English speakers had a lower rate of DLI closure at the 6‐month mark compared to English speaking patients (7.7% vs. 36.8%, P = 0.028). A non‐English primary language has been found to be risk factor with regard to access to elective surgery in diverticular disease 34 as well as a risk factor for delayed treatment in breast cancer care 35 . Qualitative data from colorectal cancer survivors demonstrates that non‐English speaking patients experience a perception of discrimination in accessing healthcare 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A non-English primary language has been found to be risk factor with regard to access to elective surgery in diverticular disease 34 as well as a risk factor for delayed treatment in breast cancer care. 35 Qualitative data from colorectal cancer survivors demonstrates that non-English speaking patients experience a perception of discrimination in accessing healthcare. 36 Designing a protocol for timely DLI closure must therefore not only optimize pathways through hospital workloads but must also cater to patients of all languages.…”
Section: Discussionmentioning
confidence: 99%